Controversy of Stunning in Animal Slaughter: An Analysis of Fiqh and Fatwa in Contemporary Indonesia - Rawanita, Mesi; Mariati, Mariati (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
The practice of stunning animals before slaughter has sparked significant debate within Islamic jurisprudence, particularly regarding its compatibility with halal requirements. This article examines the controversy surrounding stunning animal slaughter from the perspective of fiqh (Islamic legal thought) and contemporary fatwa issued by Indonesian ulama (Islamic scholars). Drawing upon primary sources, including fatwas and scholarly discourse, this research highlights the diverse opinions among Islamic scholars on the permissibility and ethicality of stunning. It explores key issues such as the interpretation of Quranic verses and hadiths related to animal welfare, the definition of a valid slaughter in Islamic law, and the socio-economic impacts of stunning on Indonesia’s meat industry. By analyzing the legal and ethical dimensions of stunning, the article contributes to the broader discussion of halal standards in the modern context and provides insights into how the Indonesian ulama navigates the balance between tradition and contemporary practices. The findings underscore the ongoing need for clarity and consensus on the issue, as divergent rulings affect both religious observance and the livestock market.